2002
DOI: 10.1080/07060660209507022
|View full text |Cite
|
Sign up to set email alerts
|

Infection process ofEntomosporium mespilion leaves of saskatoon,Amelanchier alnifolia

Abstract: The infection process for Entomosporium leaf spot of saskatoon (Amelanchier alnifolia) was evaluated with scanning electron microscopy. Following treatment with a conidiospore suspension of Entomosporium mespili, detached leaves of saskatoon cultivars were fixed at various times during disease development (2, 5, 8, and 12 days postinoculation). Scanning electron microscopy showed that conidiospore germination occurred rapidly, usually by the extrusion of a single major germ tube from the larger of two body cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A dry period may help to desiccate the surface of mature acervuli. Rainwater would then be able to wash conidia from the surface of the exposed acervuli (Ronald and St-Pierre 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A dry period may help to desiccate the surface of mature acervuli. Rainwater would then be able to wash conidia from the surface of the exposed acervuli (Ronald and St-Pierre 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A slender appendage is commonly found on the apical and lateral cells. The production of conidiospores was shown to cause rupture of the acervuli surface and permit release of the conidia contained within (Ronald and St-Pierre 2002). Wind and rain splash are the critical components in epidemic development of many diseases (Madden 1997), and although no specific studies were conducted, Lange and Bains (1995) have observed that heavy rainfall is the most important environmental factor contributing to entomosporium leaf and berry spot in saskatoon orchards.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation